Three Essays on Global Climate Policy, Environmental R&D, Mergers, and Corporate Social Responsibility - Wang, Chenyu (Université d'Ottawa / University of Ottawa, 2019)
Chapter 1: The Role of Technological Innovation in Global Climate Policy: In the first chapter, we build a dynamic model of the global economy and climate with three endogenous knowledge stocks. We confirm that the contribution of induced R&D in global climate change is shown to be very sensitive to the elasticity of substitution between energy and other factors of production. Since growth patterns of all types of research depend on whether inputs are gross complements or gross substitutes. Second, the duplication externality. Induced R&D generates a lower abatement cost reduction if we externalize duplication in the business as usual scenario. We exclude duplication in the business as usual scenario since a research institute is based on their contract to do their research. As long as they generate research outputs they would receive payments, they recognize the duplication but they think they will get paid for producing it whether their outputs have been duplicated or not. In reality, agents use too much R&D in the business as usual scenario because they do not take into account the duplication externality. Thus, when the social planner does the optimal scenario, the additional benefits of R&D may not be very much at all. Third, the initial level of research expenditure. Higher initial levels of energy related R&D shares would create a market size effect, leading to an increased contribution of induced R&D. Gerlagh (2008) uses much higher initial energy related shares whereas our research’s estimates are much lower, we find this difference would affect the size of the effects of the induced R&D. Fourth, the inter-firm knowledge spillovers. Firms are not successful in capturing all the benefits they create, as many benefits flow out into other firms free of charge. These benefits are called inter-firm knowledge spillovers. Fifth, first-best and second-best policies. The first-best policy fully internalizes the inter-firm knowledge spillovers, which leads to increases in the levels of all types of research whereas the second-best policy does not internalize it, which leads to induced changes in research resulting from the carbon tax affecting pre-existing market distortions. Sixth, a research dividend effect and tax burden effect. The tax may induce an increase in research expenditure, which would increase the welfare and consumption levels. Finally, the results demonstrated that induced R&D has a limited role on the abatement cost reduction of greenhouse gas emissions, overall. Chapter 2: Environmental Policy, Mergers and Environmental R&D with Spillovers: Our research topic is “Environmental Policy, Mergers and Environmental R&D with Spillovers”. This project lies at the frontier between environmental economics and industrial organization. We use a duopoly setting of a three-stage game; in the first stage, the government chooses an emission tax and aims for maximizing welfare; in the second stage, firms use R&D to reduce their emissions; in the last stage, firms compete a la Cournot with differentiated products. We focus on two policy regimes and three scenarios, namely regimes of competition and merger and scenarios of commitment, non-commitment, and exogenous tax. The study focuses on two major questions: (1) what is the effect of merger on R&D, and the effect of commitment on R&D? (2) what is the effect of merger and commitment on the economy? Results are obtained through numerical simulations of the model. We find that: (i) Merger has a positive effect on R&D under non-commitment and the exogenous tax scenarios. (ii) Under commitment, if goods are imperfect substitutes or homogenous, merger has a negative effect on R&D; if goods are complements or independent, merger has a positive effect on R&D. (iii) For any types of goods under any regime, commitment has a negative effect on R&D. Chapter 3: Monopoly with Corporate Social Responsibility and Environmental R&D: Our research topic is the effect of the monopolist with corporate social responsibility in the presence of environmental R&D. This project lies at the frontier between environmental economics and industrial organization. We model a monopolist with corporate social responsibility setting in a three-stage game; in the first stage, the regulator determines the emission tax to maximize welfare; in the second stage, the monopolist determines R&D to maximize its objective function; in the third stage, the monopolist determines outputs to maximize its objective function. The study focuses on one major question: under the structure of monopoly with corporate social responsibility, if we change the parameters of R&D technology parameter, the degree of social responsibility, and product differentiation, what are the effects on profit, R&D, environmental damage, consumer surplus, and welfare? We find that: (1) increasing R&D technology parameter enhances welfare in terms of higher consumer surplus and lower damage, while also leading to increases in R&D and decreases in profit; (2) increasing the degree of social responsibility increases R&D and welfare in terms of higher consumer surplus and profit, but also increases the damage; and (3) increasing product differentiation increases profit, R&D, and welfare; it also increases the damage but decreases consumer surplus.
Keywords: Environmental Economics; Industrial Organization